2020
DOI: 10.1038/s41421-020-0142-6
|View full text |Cite
|
Sign up to set email alerts
|

Structural and functional insight into the effect of AFF4 dimerization on activation of HIV-1 proviral transcription

Abstract: Super elongation complex (SEC) is a positive regulator of RNA polymerase II, which is required for HIV-1 proviral transcription. AFF1/4 is the scaffold protein that recruits other components of SEC and forms dimer depending on its THD domain (TPRL with Handle Region Dimerization Domain). Here we report the crystal structure of the human AFF4-THD at the resolution of 2.4 Å. The α4, α5, and α6 of one AFF4-THD mediate the formation of a dimer and pack tightly against the equivalent part of the second molecule in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 38 publications
1
12
0
Order By: Relevance
“…In silico modeling of most of the identified missense variants is hampered by the lack of reliable AFFs structural information with the exception of the CHD that is important for dimerization and the ALF that contains the degron and the ELL-binding domains (ELLbow, see below) 44,45 . The p.(Gln1020Arg), p.(Val1036Ile), p.(Arg1186Gln) and p.(Gly1215Val) variants fall within the CHD ( Figure 1A ).…”
Section: Resultsmentioning
confidence: 99%
“…In silico modeling of most of the identified missense variants is hampered by the lack of reliable AFFs structural information with the exception of the CHD that is important for dimerization and the ALF that contains the degron and the ELL-binding domains (ELLbow, see below) 44,45 . The p.(Gln1020Arg), p.(Val1036Ile), p.(Arg1186Gln) and p.(Gly1215Val) variants fall within the CHD ( Figure 1A ).…”
Section: Resultsmentioning
confidence: 99%
“…Although the crystal structure of AF4-AFF4 heterodimer is not available, that of the homodimer of AFF4 CHD domain has been determined (PDB: 6R80) [ 168 , 207 , 208 ]. Biochemical including mutagenesis studies revealed that the interface between AF4 and AFF4 heterodimer overlap with that of AFF4 homodimer, thanks to a high degree of homology between the two CHD domains.…”
Section: Ppis Involving Mll1 Fusion Proteinsmentioning
confidence: 99%
“…[135][136][137][138][139] Although antiretroviral therapies (ARTs) have been used as a major treatment for AIDS, HIV-1 remains incurable due to its mutation, latency, and destruction of T cells. [140][141][142][143][144][145][146][147][148][149][150] Because HIV remains one of the most significant public health problems worldwide, elucidating each step of the HIV life cycle is necessary to develop more effective therapies.…”
Section: Tmem16f and Hiv Infectionmentioning
confidence: 99%